Hantavirus infections in Southeastern Europe – Epidemiology, outbreak dynamics, and One Health preparedness: A narrative review - Edmond Puca; Rok Čivljak; Aleksandra Barac; Luka Laura; Goran Stevanovic; Magdalena Baymakova; Sotirios Tsiodras; Casandra Bulescu; Gramoz Bunjaku; Jurica Arapović (Biomolecules and Biomedicine, 2026)
Human-pathogenic orthohantaviruses are significant rodent-borne zoonotic pathogens in Europe. Southeastern Europe (SEE) is a distinct endemic region where Dobrava-Belgrade virus (DOBV) and Puumala virus (PUUV) co-circulate, causing hemorrhagic fever with renal syndrome (HFRS) of varying severity. This narrative review synthesizes the epidemiology, transmission dynamics, clinical characteristics, ecological drivers, and public health challenges of hantavirus infections across SEE, identifying priorities for regional preparedness. We searched PubMed, Scopus, and Web of Science from their inception through June 2026, supplementing with reference screening. Regional epidemiological patterns were assessed descriptively using national surveillance data, European surveillance reports, published studies, and available population-based incidence estimates. Long-term surveillance reveals persistent endemic transmission with significant geographic and interannual heterogeneity. Slovenia and Croatia exhibit the highest cumulative burden and most pronounced periods of increased HFRS activity. Several years—2008, 2012, 2014, 2017, 2019, 2021, and 2023—showed partially synchronized increases across multiple neighboring countries. These patterns align with shared ecological influences, including rodent population fluctuations, mast-seeding events, and climatic variability. However, local ecology, human exposure, and differences in surveillance capacity modify their magnitude. The coexistence of generally milder PUUV-associated disease and more severe DOBV-associated HFRS further distinguishes SEE's clinical landscape. Therefore, hantavirus epidemiology in SEE is best understood as an interconnected regional ecological system. Integrated human, animal, environmental, and genomic surveillance within a coordinated One Health framework is crucial for improving outbreak prediction, cross-border preparedness, and future disease control.